Does Green-Person-Organization Fit Predict Intrinsic Need Satisfaction and Workplace Engagement? - Hicklenton, Carol; Hine, Donald William; Loi, Natasha Maria (Frontiers in Psychology, 2019)
The current study assessed whether high green-person-organization fit (GPO; the extent to which an organization’s commitment to pro-environmental outcomes is congruent with its employees’ environmental values) predicts employees’ intrinsic need satisfaction and engagement in the workplace. The sample consisted of 818 full-time Australian workers, sourced from an online panel. Consistent with the GPO model, pro-environmental work climate was a more potent predictor of intrinsic need satisfaction and engagement for employees with strong ecocentric values that those with weak ecocentric values. Mediation analyses revealed that the effect of work climate on employee engagement was fully mediated by intrinsic need satisfaction, and this effect was strongest when GPO fit was high. Overall, our findings suggest that organizations with pro-environmental work climates that match their employees’ values have more satisfied and committed workforces.